Kakovost problemov, obravnavanih pri problemskem učenju - Gönc, Vida (Obzornik zdravstvene nege, 2016)
Introduction: With problem-based learning the context of learning has changed. The use of problem-based learning promotes critical thinking, group interaction, and the use of theory in practice. The purpose of the research was to determine the nursing students' assessment regarding the quality of problems used in the context of problem-based learning. Methods: The study employed methods of quantitative non-experimental research and a survey data collection. A total of 169 nursing students participated in the study. The data were processed by descriptive statistics, t-test and correlation analysis. The statistical significance was tested at a 5% risk level. Results: The average of all items which were related to the assessment of the quality of problems in the context of the problem-based learning was high ( > 4 out of 5). Depending on the mode of study (t = -1.333, p = 0.558) and gender (t = 0.236, p = 0.354), there is no difference in the quality of self-assessment of problems within the problem-based learning. The findings of the study show that there is a statistically significant difference in self-assessment of the quality of problems in the context of the problem-based learning with regard to the employment in nursing (t = 2.109, p = 0.04) and that there is a weak positive correlation (r = 0.190, p = 0.002) between the age and the self-assessment of the quality of problems in the present problem-based learning. Discussion and conclusion: Research results reveal high average values of the quality of problems used in the problem-based learning, which result in positive encouragement of students for self-directed learning, increased interest in a learning unit, improved motivation, better communication skills and critical thinking. Further research would be needed to explore the impact of problem-based learning on learning outcomes and the introduction of problem-based learning in all learning units of the nursing study programme.
Keywords: evaluation; evalvacija; nursing care; problemi; problems; student; students; študenti; zdravstvena nega